The story of a fierce bad rabbit - Potter, Beatrix, 1866-1943 (Potter, Beatrix, 1866-1943. Original Peter Rabbit books, 2002)
The fierce bad rabbit takes away the nice gentle rabbit's carrot nuts with the other squirrels. But, a hunter with a gun takes the fierce bad rabbit's tail and whiskers.